Use of Endoscopic Ultrasound in a Diagnostic Dilemma: Metastatic Breast Cancer to the Stomach - Laura L. Ulmer; Ian Cormier; Lokesh K. Jha; Shailender Singh; Kurt W. Fisher; Alexander T. Hewlett (Case Reports in Gastrointestinal Medicine)
A 55-year-old woman presented with persistent nausea, vomiting, and weight loss previously attributed to Ménétrier’s disease. On further workup, she was found to have metastatic lobular breast carcinoma causing gastric outlet obstruction, diagnosed by endoscopic ultrasound with fine needle aspiration after previous gastric mucosal biopsies were unremarkable. In most reported cases of gastric metastasis from breast cancer, a diagnosis was established by mucosal biopsy. This case is an important reminder that mucosal biopsies can be negative in about 20% of patients with gastric metastasis, which may lead to a delay in diagnosis and treatment. Gastroenterologists should be diligent in taking deeper biopsies if there is a suspicion for gastric metastasis.